Civilians at war: focusing on the Israeli-Palestinian conflict and scrutinizing the doctrine of non-combatant immunity - Liu, Xia (Frontiers in Political Science, 2024)
The principle of non-combatant immunity was codified in the Code of International Law and developed into an important foundation for the doctrine of just war, whose origins can be traced to the moral imperative of religious support. The doctrine advocates that persons deemed innocent should be protected from the threat of war, and it is the most widely recognized and deeply rooted moral constraint on the conduct of war. However, the principle of non-combatant immunity has not really deterred the outbreak of war, leaving the international community committed to utopian ideals. In the contemporary context of the Israeli-Palestinian conflict, the principle of non-combatant immunity has been rendered ineffective as civilians are forced to be on the frontlines of both sides of the war. The principle of “just war” seems to have taken on a new basis, with self-defense becoming the pretext for justifying war, and the international community unable to rescue civilians from the flames of war amidst the outcry. There is an urgent need for the international community to re-examine and re-evaluate the immunity of non-combatants, and to limit the use of war as a “legitimate” means of resolving international conflicts. This article calls for a critical assessment of the normativity and effectiveness of the existing law on the principle of non-combatants, and a rethinking of how to construct a more rational and high-level principle to enhance the protection of non-combatants.